Pemetaan Loyalitas Karyawan Pada Bank Syariah Indonesia (BSI) Tenggarong - Iskandar, Iskandar; Johansyah, Johansyah; Indrianti, Eti (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2023)
The purpose of this study was to find out and examine how high the level of compliance, responsibility, dedication, integrity, dedication and internal service quality at work in Bank Syariah Indonesia (BSI) Tenggarong employee loyalty and examine the mapping of Bank Syariah Indonesia (BSI) Tenggarong Employee Loyalty. The population in this study was taken from the number of employees at Bank Syariah Indonesia (BSI) Tenggarong, which totaled 33 people. With a population of employees below 100, the number of samples that the researcher will use is the same as the population, namely 33 people. In conducting research the method used by researchers is a census, in which the sample is taken as a whole without exception. The results of the study show that Bank Syariah Indonesia (BSI) Tenggarong employee loyalty as measured by the six indicators yields the fact that the responsibility indicator has the highest value, followed sequentially by compliance indicators, integrity indicators, internal service quality indicators, dedication indicators and service indicators. lowest. The results of the mapping show that the responsibility indicator is the highest value in the employee loyalty study at Bank Syariah Indonesia (BSI) Tenggarong. this proves that employees have the desire to complete the tasks assigned correctly. Meanwhile, the result of the dedication indicator is the lowest value in the research on employee loyalty at Bank Syariah Indonesia (BSI) Tenggarong. this proves that the low level of employees giving thoughts to Bank Syariah Indonesia (BSI) Tenggarong.